Correlation of Self-Regulation on Enhancing Adolescent Self-Reliance in Preventing Drug Abuse in Medan City - Eka Prahadian Abdurahman (Jurnal Multidisiplin Madani, 2023)
Referring to the World Drugs Report 2020, there has been an increase in global drug use and illicit substance abuse. In 2018, approximately 269 million people worldwide were using drugs. This study aims to examine the influence of self-regulation on the resilience of teenagers in preventing drug abuse. This is a quantitative analytical study with a cross-sectional design. The study population consists of 17,906 students from public vocational schools in Medan City, with a sample of 200 individuals selected through random cluster sampling. The instruments used were questionnaires, and data analysis was conducted using univariate, bivariate, and multivariate analyses with simple regression tests. The data processing results from the 200 student respondents revealed that 49.5% were male and 50.5% were female. Among them, 56.5% had low levels of self-regulation, while 43.0% exhibited sufficient resilience. Bivariate analysis using the Chi-Square test yielded a r-value of 0.0001 (r < 0.05), indicating a significant relationship between self-regulation and teenage resilience in Medan City regarding drug abuse prevention. Referring to the findings of this study can be generally understood that self-regulation influences adolescent resilience in preventing drug abuse